2010
DOI: 10.1002/ajpa.21421
|View full text |Cite
|
Sign up to set email alerts
|

Comparative microcomputed tomography and histological study of maxillary pneumatization in four species of new world monkeys: The perinatal period

Abstract: In anthropoid primates, it has been hypothesized that the magnitude of maxillary sinus growth is influenced by adjacent dental and soft tissue matrices. Relatively, little comparative evidence exists for the perinatal period when secondary pneumatization is at its earliest stages in some primates. Here, dental and midfacial variables were studied in a perinatal sample of four anthropoid primates, including three callitrichines (Leontopithecus, Saguinus, and Callithrix) and Saimiri boliviensis. In the latter sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(50 citation statements)
references
References 38 publications
4
46
0
Order By: Relevance
“…Because the morphology and association of the components of anatomical systems are affected by developmental and functional factors, we expected that traits sharing spatial, functional or developmental attributes are linked and vary in a coordinated manner (Olson & Miller, ). The extent of the maxillary sinus, which is the most studied of the paranasal sinuses, is known to be influenced in New World monkeys by the relative dental size and the growth of adjacent skeletal structures of the maxilla; histomorphometric studies have confirmed that the growing maxillary sinus extends into areas without constraints (Smith et al, ). In humans, the maxillary sinus is larger in individuals with larger faces and it accommodates in the available space left by the lateral nasal walls: individuals with narrower nasal cavities present larger maxillary sinuses (Butaric & Maddux, ; Butaric et al, ; Holton et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because the morphology and association of the components of anatomical systems are affected by developmental and functional factors, we expected that traits sharing spatial, functional or developmental attributes are linked and vary in a coordinated manner (Olson & Miller, ). The extent of the maxillary sinus, which is the most studied of the paranasal sinuses, is known to be influenced in New World monkeys by the relative dental size and the growth of adjacent skeletal structures of the maxilla; histomorphometric studies have confirmed that the growing maxillary sinus extends into areas without constraints (Smith et al, ). In humans, the maxillary sinus is larger in individuals with larger faces and it accommodates in the available space left by the lateral nasal walls: individuals with narrower nasal cavities present larger maxillary sinuses (Butaric & Maddux, ; Butaric et al, ; Holton et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Some evolutionary, clinical, and surgical studies have provided evidence of association between the morphology of paranasal sinuses and the surrounding bony structures (e.g., Fatu et al, ; Flanigan et al, ; Hamdy & Abdel‐Wahed, ; Park et al, ; Rahmati et al, ; Smith et al, ; Ć toković et al, ; Zollikofer & Weissmann, ) and between sinuses and stature in humans (Ruf & Pancherz, ). Studies comparing different species of mammals have shown that the FS volume is positively associated with skull size (Curtis et al, ; Farke, ; Zollikofer et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…This implies that sinus variation, including the patterns of presence/absence and the degree of expansion, depends on the limitations to pneumatization imposed by the surrounding facial architecture during the ontogenetic process. This structural hypothesis is supported by the finding that species lacking the maxillary sinus present specific orofacial features that probably prevent maxillary pneumatization in the early stages of the ontogenetic process (Smith et al ., , ). The correlation between paranasal sinus size and skull architecture further supports the structural hypothesis (Koppe, Rae & Swindler, ; Zollikofer et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Specimens were selected from a larger sample of infant cadavers currently housed in the laboratory of TDS that either died postnatally or were stillborn. There are inherent difficulties in knowing the precise somatic age of infant primates (see discussion by Smith and Leigh, 1998 [24]; Smith et al, 2011 [25]). To minimize the possibility of including underdeveloped perinatal specimens in our analysis, fetuses or stillbirths that were clearly premature were excluded from the study.…”
Section: Methodsmentioning
confidence: 99%